ปัจจัยทุนจิตวิทยาเชิงบวกที่ส่งผลต่อการหมดไฟในการทำงานของข้าราชการรุ่นใหม่ในสำนักการสอบสวนและนิติการ กรมการปกครอง - พิรุฬห์พร เพียงพิมพ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
"A study of positive psychological capital factors affecting job burnout of the government officers: a case study of Investigation and Legal Affairs Bureau, Department of Provincial Administration" is qualitative research. The objectives of the study were to understand the most important of positive psychological capital factors that affect job burnout of the government officers, to analyze the impact of job burnout of the government officers and to find the solutions of job burnout of the government officers in Investigation and Legal Affairs Bureau, Department of Provincial Administration. The research applies an in-depth interview of three sample groups, namely 1) the early Gen-Y group, 2) the middle Gen-Y group, and 3) the late Gen-Y group The findings indicated that the Gen-Y group had positive psychological capital factors. However, the factors that should be developed were as follows: 1) Confidence, 2) Hope, and 3) Optimism, meanwhile the resilience is the factor that the organization should maintain with the Gen-Y group. In order to prevent the emotional exhaustion, the depersonalization, and the decreased occupational accomplishment, the organization has to develop the positive psychological capital factors because it not only prevent job burnout but also make a good member of the organization.